A conceptual paper of entrepreneurial intention among undergraduate student in Sabah - Kelvin Yong; Chang, Dyana Mui Ling; Irma Wani Othman (Global Academic Excellence, 2022)
The purpose of this conceptual paper is to investigate the link between entrepreneurial passion and entrepreneurial education in relation to entrepreneurial intention. The unemployment rate in Sabah continue to rise from 5.8% (2020) to 8.0% (2022), where the unemployment rate increased by 2.2% between 2020 and 2021. By 2024, there may be a quarter of a million youngsters unemployed in Sabah, according to the Sabah and Labuan Skills Training Centre-National Dual Training System Association. The study uses quantitative approach in this investigation. The theory planned behaviour (TPB) that connected the relationship between entrepreneurial passion, entrepreneurial education, and entrepreneurial intention served as the foundation for this study. The selected respondents are final-year students who have taken an entrepreneurship course as part of their studies. A convenience sampling will be use in this study to collect data from respondents using a survey questionnaire. The survey questionnaire will be distributed to respondents via online Google forms. The data generated from the sample will be transcribed and analysed using the Statistical Package for Social Sciences (SPSS) and Smart PLS 4. Previous findings shows that there is positive relationship between entrepreneurial passion, entrepreneurial education and entrepreneurial intention. The sub-dimension for entrepreneurial passion is based on inventing, founding and developing. The research findings have implication for academics of entrepreneurship education, entrepreneurship central, program evaluators, government agency and policymakers.